The DFT study on the electronic structure of boronic acid derivatives and its esters with fructose - Kur, Katarzyna; Kowalska-Baron, Agnieszka; Miller, Ewa (Wydawnictwo Politechniki Łódzkiej, 2018)
Theoretical investigations are carried out to examine the geometrical structure and parameters of electron transitions to the lowest excited states of two boronic acid derivatives: 3-aminophenylboronic acid and 3-(acetamidomethyl)phenyl boronic acid and its cycling esters with fructose, using the DFT based 6-31 G(d,p) method. The most stable ester isomer of each acid has been selected. Predicted excitation wavelength are shorter (less than 0.5 eV) than experimental ones, what is in a good agreement considering limitations of the DFT method. In case of almost every calculated molecule the analysis of electronic transitions shows that transition S0→S1 involves electron transfer mainly from the HOMO to LUMO orbital.
Keywords: boronic acid derivatives; TD-DFT method; boronic esters with fructose; pochodne kwasu boronowego; metoda TD-DFT; estry boronowe z fruktozą